Temporal trend of QRS voltage amplitude on surface sensing in patients with arrhythmogenic cardiomyopathy implanted with a subcutaneous ICD. (19th May 2022) - Casula, M; De Toni, C; Pignalosa, L; Savastano, S; Schintu, B; Sanzo, A; Scalone, A; Tola, G; Corda, M; Vicentini, A; Rordorf, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Previous studies have reported a significant decrease in ventricular sensing amplitude during follow-up in patients with arrhythmogenic cardiomyopathy (ACM) implanted with trans-venous implantable cardioverter defibrillator (ICD). No data are yet available on sensing amplitudes values over time for subcutaneous ICD (S-ICD). Low QRS voltage on surface ECG is one of the diagnostic clues in ACM. This, together with the progressive nature of the disease and the not-negligible incidence of inappropriate shocks due to oversensing, raise safety concerns on the use of S-ICD in this population. Aim: The aim of this study was to evaluate the trend of QRS amplitude on subcutaneous ECG (S-ECG) over time in patients with ACM implanted with S-ICD. Methods: We conducted a retrospective analysis on a cohort of consecutive patients with ACM implanted with S-ICD in two tertiary centers, prospectively enrolled in the home-monitoring program. The S-ECGs recorded by the S-ICD at the time of first and last data transmission were analyzed. The voltage amplitude was estimated for each QRS complex available, and the values obtained were compared between the two time points (i.e. baseline and last follow-up available). The primary endpoint of our study was the proportion of patients in which the decrease of QRS amplitude during follow-up was statistically significant. Results: Eleven patients (1 female, 9%) were enrolled in this study. The mean age was 43±10 years. An exclusive right ventricular involvement was reported in 5 patients (46%), 2 patients (18%) had an exclusive left ventricular, and 4 (36%) a biventricular involvement. Three patients (27%) were implanted in secondary prevention. During a median follow-up of 9 months (IQR 6-17), 6 patients (55%, 95%CI 24-84%) experienced a statistically significant reduction in the S-ECG QRS amplitude (Figure A). Considering these 6 patients, the mean absolute reduction was -0.46±0.32 mV corresponding to a relative reduction of -19%±11%. Moreover, we found a statistically significant correlation between follow-up duration and QRS amplitude relative reduction (r=-0.89, p=0.018, Figure B). No patients experienced inappropriate shocks. Conclusions: In a cohort of ACM patients implanted with S-ICD the majority of patients experienced a significant reduction in the amplitude of QRS voltage during follow-up, confirming a potential safety concern on the use of S-ICD in this population. Further studies are needed to investigate this issue.